X :3 + 625 = 654
X = (654 - 625) : 3
X = 27 : 3
X = 9
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
Vậy x = 87
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
Vậy x = 87
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
Vậy x = 87
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
Vậy x = 87
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
Vậy x = 87
x : 3 + 625 = 654
x : 3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87 ( Bạn Nguyen Thi Thu Phuong trả lời sai rồi!!!! )
thu phương sai rồi
x : 3 + 625 = 654
x :3 = 654 - 625
x : 3 = 29
x = 29 x 3
x = 87
vậy x = 87
x:3+625=654
=>x:3 =654-625
=>x:3 =29
=>x =29*3
=>x =87
Có đúng không các bạn ?